PERANAN BADAN PENASEHAT PEMBINAAN PELESTARIAN PERNIKAHAN (BP4) DALAM MEMEDIASI PERCERAIAN: Studi Kasus Kecamatan Ciampea Bogor - Fajar Romadon; Eka Sakti Habibullah; Fachri Fachrudin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2017)
No one ever hopes to experience the rift of the household life they have built. Various problems, such as frequent quarrels, loss of sense of compatibility, domestic violence, economic factors, and adultery are often the source of problems in the breakdown of household relationships that lead to divorce. In fact, every couple will make every effort to end their divorce. However, not all household lives run so that the decision to divorce is a last resort for married couples. In the last three years (2015-2017) the trend of decision cases (inkracht) divorce in the Religious Courts throughout Indonesia has increased. For example, the number of divorce divorce cases (husband) and divorce (wife) in 29 Religious High Courts in 2015 recorded a total of 394,246 cases (divorce divorce: 113,068 and divorce: 281,178 cases) and 353,843 litigation cases (divorce divorce : 99,981 and divorce: 253,862 cases. Mediation is one of the processes to bridge negotiations conducted by the Marriage Development Advisory Board (BP4) as a work unit under the KUA in each sub-district. This study uses qualitative methods and case studies through observation and interviews. The focus of the study regarding the role of BP4 in mediation is to minimize divorce rates.Keyword: divorce, BP4, mediation.